2018
DOI: 10.7717/peerj.5201
|View full text |Cite
|
Sign up to set email alerts
|

Age of onset of cannabis use and decision making under uncertainty

Abstract: ObjectiveCannabis, like other substances, negatively affects health, inducing respiratory problems and mental and cognitive alterations. Memory and learning disorders, as well as executive dysfunctions, are also neuropsychological disorders associated to cannabis use. Recent evidence reveals that cannabis use during adolescence may disrupt the normal development of the brain. This study is aimed to analyze possible differences between early-onset and late-onset cannabis consumers.MethodWe used a task based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…In humans, earlier initiation of tobacco smoking has been associated with deficits in response inhibition [76], sustained attention [76], and working memory [71]. Likewise, earlier use of cannabis during adolescence has been associated with poorer performance on a number of cognitive tasks indexing decision-making [77], verbal IQ [78], impulsivity [79], executive functions [80, 81] and memory [82], with suggestions that cannabis use during adolescence may perturb developmental processes such as white matter development and synaptic pruning [83]. Importantly, many of these studies are cross-sectional and collect retrospective age of onset data, and there is a need for prospective and longitudinal studies tracking adolescents before and after initiation of substance use to clarify the links between brain health and adolescent substance use [84, 85].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, earlier initiation of tobacco smoking has been associated with deficits in response inhibition [76], sustained attention [76], and working memory [71]. Likewise, earlier use of cannabis during adolescence has been associated with poorer performance on a number of cognitive tasks indexing decision-making [77], verbal IQ [78], impulsivity [79], executive functions [80, 81] and memory [82], with suggestions that cannabis use during adolescence may perturb developmental processes such as white matter development and synaptic pruning [83]. Importantly, many of these studies are cross-sectional and collect retrospective age of onset data, and there is a need for prospective and longitudinal studies tracking adolescents before and after initiation of substance use to clarify the links between brain health and adolescent substance use [84, 85].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies examining associations between CU and DM have relied upon adult samples, while less is known about these relationships during adolescence. Poorer or riskier DM has been cross-sectionally documented among regular adolescent cannabis users [43,44], adolescents with CUD in full remission [45] and adults who initiated use during adolescence [46], with null results reported in only one cross-sectional [47] and one longitudinal study [48]. Similar to adult studies, findings from cross-sectional and prospective neuroimaging work suggest that adolescent chronic cannabis users show alterations in brain activation in regions such as the anterior cingulate cortex, ventromedial prefrontal cortex and orbitofrontal cortex while performing DM tasks [37,45,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other studies assessing elements of reward learning have shown more impaired performance with higher chronicity frequency , THC potency and dependence . However, others have found no relationship with reward learning and severity of cannabis use parameters, mainly chronicity (Alameda-Bailén et al, 2018;Tamm et al, 2013;Verdejo-García et al, 2013). Studies in animal models have shown that THC, particularly in high doses, results in failure to develop reward associations in conditioned place preference paradigms, or even led to place aversion Sañudo-Peña et al, 1997;, and attenuated electrical self-stimulation (Katsidoni et al, 2013;Wiebelhaus et al, 2015).…”
Section: Relationship Between Reward Learning and Cannabis Use Charac...mentioning
confidence: 99%